Efficacy of topical mesenchymal stem cell exosome in Sjögren’s syndrome-related dry eye: a randomized clinical trial - Azam Habibi; Amir Khosravi; Masoud Soleimani; Mahmood Nejabat; Mahintaj Dara; Negar Azarpira (BMC Ophthalmology)
Abstract Background Sjögren’s syndrome (SS) is a chronic inflammatory autoimmune disorder affecting salivary and lacrimal glands, leading to distressing ocular symptoms. Existing therapeutic approaches for SS-associated dry eye syndrome (DES) show insufficient efficacy. This study investigates the use of topical MSC-derived exosomes in primary SS-related DES. Methods In phase 1 and 2, triple-blinded, randomized trial, two vials of eye drops are given to each participant, one with code A and one with code B and only the supervisor knows the content of each vial. The treatment group (n = 8 eyes) received 10 µg of MSC-derived exosomes twice daily for two weeks and the control group (n = 8 eyes) received Phosphate buffered saline(PBS) for their respective eyes. Safety was assessed through ophthalmic exams, while DES assessment tests evaluated treatment effectiveness. Non-parametric tests employed to examine assumptions. The differences of ocular examination results between day 0 and month 3 were analyzed using a paired Student’s t test. Measurement data that were not normally distributed are represented by the median (interquartile range), and comparisons were performed using the Wilcoxon rank-sum test. Results The treatment showed promising results, with significant improvements observed in various indicators such as reduced Ocular Surface Disease Index scores, increased tear secretion, lower fluorescein scores, and longer tear-film break-up time before and after treatment and between the controls and the treated groups. Our results showed a significant increase in multifunctional proteins such as Epidermal Growth Factor and thrombospondin-1 and conversely, the levels of pro-inflammatory cytokines, including interleukin-6 and Matrix metalloproteinase-9 significantly decreased in tear of participant before and after treatment and between the controls and the treated groups. Conclusions Our study underscores the safety and substantial therapeutic potential of using MSC-derived extracellular exosomes eye drops to treat SS-associated DES. Trial registration IRCT20211102052948N1 The study protocol has been approved in Iranian Registry of Clinical Trials at 2022-04-20.